PERAN KEPOLISIAN DALAM PENANGANAN TINDAK PIDANA PENCUCIAN UANG (Studi di Kepolisian Daerah Sumatera Utara) - S.H., M.Hum, Prof. Dr. Maidin Gultom; Manalu, S.H., M.H, Sahata (Universitas Quality, 2023)
This study aims to identify and understand the modus operandi of money laundering; and To know and understand the role of the police in dealing with the Crime of Money Laundering.This research is a normative juridical research that is analytical descriptive in nature, namely research that aims to provide an overview of: the causes of the occurrence of money laundering crimes and the modus operandi of money laundering crimes, criminal responsibility of perpetrators of money laundering crimes according to Law no. 8 of 2010, the role of the police in overcoming the crime of money laundering.Whereas the results of this study are 1) To anticipate the implementation of the TPPU Law, service providers must prepare themselves, especially the administration system for prospective customers, the investigation system and strategy that will be carried out by a special unit, and vice versa, the general public must understand and understand money laundering, in addition it is necessary to have cooperation between related parties and other countries in eradicating money laundering crimes, without such cooperation the crime of laundering will continue to develop; and 2) The role of the North Sumatra Regional Police in tackling money laundering crimes according to Article 1 paragraph (5) of Law no. 2 of 2002 concerning the Indonesian National Police, namely the role of the National Police which is in line with the Police functions stipulated in Law no. 2 of 2002 concerning the Police and efforts to combat money laundering in the criminal justice system, namely carrying out preliminary examinations. Preliminary examinations are carried out in the sense that an investigation is carried out against a person suspected of committing a crime. A criminal case reaches the hands of Polri investigators.